Clinical Assessment of Tribulus terrestris Extract in the Treatment of Female Sexual Dysfunction - Gama, Carlos R. B. [UNESP]; Lasmar, Ricardo [UNESP]; Gama, Gustavo F.; Abreu, Camila S.; Nunes, Carlos P.; Geller, Mauro; Oliveira, Lisa; Santos, Alessandra (Libertas Academica Ltd, 2014)
This is a qualitative-quantitative study based on hospital records of female patients of reproductive age, presenting sexual dysfunction, and treated with 250 mg Tribulus terrestris extract (1 tablet thrice daily for 90 days). Safety monitoring included vital signs, physical examination, laboratory tests, and occurrence of adverse events. Efficacy analysis included results of the Female Sexual Function Index (FSFI), dehydroepiandrosterone (DHEA) levels together with total and free testosterone, and the patient and physician assessments. There was a statistically significant improvement in total FSFI scores (P < 0.0001) post-treatment, with improvement among 106 (88.33%) subjects. There was a statistically significant (P < 0.0001) increase in the level of DHEA, while the levels of both serum testosterone (P = 0.284) and free testosterone decreased (P < 0.0001). Most adverse events recorded were related to the gastrointestinal tract. Physical examination showed no significant changes post-treatment. Based on the results, it is concluded that the T. terrestris extract is safe and effective in the treatment of female sexual dysfunction.
Keywords: Tribulus terrestris; Female sexual dysfunction; Female sexual function index